Capturing news, capturing democracy Trump and the voice of America - Wright, Kate 1974-; Scott, Martin 1982-; Bunce, Melanie (Oxford University Press, 2024)
"This book uses rare interviews and an analysis of private correspondence and internal documents, to explain why and how Voice of America (VOA) became intensely politicized from 2020-2021. It analyzes how political appointees, White House officials and right-wing media influenced VOA-changing its reporting of the Black Lives Matter movement, the presidential election, and its contested aftermath. Trump allies took control of the network's financial and human resources, dominated its governance structures, and instigated intimidating investigations into journalistic "bias." Some journalists tried to resist, but others were too exhausted and fearful, particularly those in the organization's language services. The book puts these events in historical and international context-and develops a new analytical framework for understanding government capture and its connection to broader processes of democratic backsliding. It argues that there is currently too little to prevent a future US administration with authoritarian tendencies from capturing VOA and converting it into a major domestic news organization. For this reason, it uses empirical research to recommend practical ways of protecting the network and other international public service media better in future"--
Includes bibliographical references and index
Keywords: Trump, Donald -- 1946-; Voice of America; Politische Berichterstattung; Rundfunk; USA; Voice of America (Organization); Public broadcasting / Political aspects / United States; Broadcasting policy / United States; Public broadcasting / Political aspects; Broadcasting policy; Radiodiffusion publique - Aspect politique; Radiodiffusion publique - Aspect politique - États-Unis; Radiodiffusion - Politique gouvernementale; Radiodiffusion - Politique gouvernementale - États-Unis